Perilaku Menyakiti Diri Sendiri Bentuk, Faktor dan Keterbukaan Dalam Perspektif Perbedaan Jenis Kelamin - Rini Rini (Universitas Persada Indonesia YAI, 2022)
Self-harm is perpetrated by both men and women. Comparison of the types, factors anddisclosures of self-harm based on the perspective of gender differences need to beresearched more. The aim is to get an idea of the differences in types, factors anddisclosures between men and women in terms of self-harm. Respondents in this study were348 people who had done self-harm with accidental sampling technique. Data is collectedby google forms which are distributed via social media. Data analysis using descriptiveapproach. The results of the analysis show that the most common types of self-harm bywomen are pulling their hair and hitting themselves, while men are more likely to hitthemselves. The women's self-harm is more triggered by factors of not being able to controltheir emotions and factors of low self-esteem and loneliness. While many men are triggeredby factors of not being able to control their emotions and cannot solve problems or cannotachieve what is expected. Both men and women have a propensity to cover up their selfharmingfrom anyone. However, in terms of choosing to tell about their self-harm to someclosest people, women have a tendency to disclosure up 6 times higher than men